Microwave treatment and pH influence on hydroxyapatite morphology and structure - Yudin A.; Ilinykh I.; Chuprunov K.; Kolesnikov E.; Kuznetsov D.; Leybo D.; Godymchuk (Godimchuk) A. Yu. Anna Yuryevna (2019, 2019)
Title screen